2012
DOI: 10.1016/j.rvsc.2011.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium supplementation with sodium selenite and selenium nanoparticles on iron homeostasis and transferrin gene expression in sheep: A preliminary study

Abstract: The present research aimed at evaluating the effects of sodium selenite and selenium nanoparticles (Se NPs) on iron homeostasis and the expression of transferrin and its receptor-binding protein genes. Twenty one Lori-Bakhtiary sheep were randomly allocated into 3 groups. Groups 1 and 2 orally received Se NPs and sodium selenite (1 mg kg(-1)) for 10 consecutive days, respectively. Group 3 served as the control. Blood and sternal bone marrow samples were collected at different supplementation intervals. Various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…In addition, decision tree-based classification analysis revealed that Fe could be a good marker for evaluating the effect of selenate for AD transgenic mice, which is consistent with the above idea that decreasing the Fe level might be a key factor for AD treatment using high-dose selenate. Although the mechanism how Se could affect Fe metabolism in the brain is still unclear, previous studies have shown that dietary Se can regulate expression of genes involved in Fe metabolism such as transferrin and its receptor genes7475. Future research is needed to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decision tree-based classification analysis revealed that Fe could be a good marker for evaluating the effect of selenate for AD transgenic mice, which is consistent with the above idea that decreasing the Fe level might be a key factor for AD treatment using high-dose selenate. Although the mechanism how Se could affect Fe metabolism in the brain is still unclear, previous studies have shown that dietary Se can regulate expression of genes involved in Fe metabolism such as transferrin and its receptor genes7475. Future research is needed to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…In agricultural domain, AgNPs have been attributed to act as plant‐growth stimulators, fungicides able to prevent rot, mould and other fungal diseases, or agents for stimulation of early fruit ripening . During the last decade, selenium nanoparticles (SeNPs) have also attracted attention to be used in agriculture due to their enhanced antioxidant and biocidal activities, as well as lower toxicity compared to the bulky selenium . Compared to other nanoparticles (NPs), SeNPs are superior as they are biodegradable with excellent bioavailability, anticancerous and anti‐inflammatory activity .…”
Section: Introductionmentioning
confidence: 99%
“…Se nanoparticles (SeNP) are considered to provide a depot formulation of Se through gradual release of dissolved Se from the particle surface. A gradual release formulation has been proposed to be desirable for safer food supplements (Kojouri, Jahanabadi, et al 2012, Skalickova et al 2017. Regarding toxicity, the hypothesis we aimed at investigating was whether SeNP have effects analogous to the molecular selenium species used in food supplements or whether they exert any particle specific toxicity.…”
Section: Introductionmentioning
confidence: 99%